# 11.12: A.12.1- Section 12.1 Answers

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$

( \newcommand{\kernel}{\mathrm{null}\,}\) $$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\id}{\mathrm{id}}$$

$$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\kernel}{\mathrm{null}\,}$$

$$\newcommand{\range}{\mathrm{range}\,}$$

$$\newcommand{\RealPart}{\mathrm{Re}}$$

$$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$

$$\newcommand{\Argument}{\mathrm{Arg}}$$

$$\newcommand{\norm}[1]{\| #1 \|}$$

$$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$

$$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\AA}{\unicode[.8,0]{x212B}}$$

$$\newcommand{\vectorA}[1]{\vec{#1}} % arrow$$

$$\newcommand{\vectorAt}[1]{\vec{\text{#1}}} % arrow$$

$$\newcommand{\vectorB}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vectorC}[1]{\textbf{#1}}$$

$$\newcommand{\vectorD}[1]{\overrightarrow{#1}}$$

$$\newcommand{\vectorDt}[1]{\overrightarrow{\text{#1}}}$$

$$\newcommand{\vectE}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash{\mathbf {#1}}}}$$

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

$$\newcommand{\avec}{\mathbf a}$$ $$\newcommand{\bvec}{\mathbf b}$$ $$\newcommand{\cvec}{\mathbf c}$$ $$\newcommand{\dvec}{\mathbf d}$$ $$\newcommand{\dtil}{\widetilde{\mathbf d}}$$ $$\newcommand{\evec}{\mathbf e}$$ $$\newcommand{\fvec}{\mathbf f}$$ $$\newcommand{\nvec}{\mathbf n}$$ $$\newcommand{\pvec}{\mathbf p}$$ $$\newcommand{\qvec}{\mathbf q}$$ $$\newcommand{\svec}{\mathbf s}$$ $$\newcommand{\tvec}{\mathbf t}$$ $$\newcommand{\uvec}{\mathbf u}$$ $$\newcommand{\vvec}{\mathbf v}$$ $$\newcommand{\wvec}{\mathbf w}$$ $$\newcommand{\xvec}{\mathbf x}$$ $$\newcommand{\yvec}{\mathbf y}$$ $$\newcommand{\zvec}{\mathbf z}$$ $$\newcommand{\rvec}{\mathbf r}$$ $$\newcommand{\mvec}{\mathbf m}$$ $$\newcommand{\zerovec}{\mathbf 0}$$ $$\newcommand{\onevec}{\mathbf 1}$$ $$\newcommand{\real}{\mathbb R}$$ $$\newcommand{\twovec}[2]{\left[\begin{array}{r}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\ctwovec}[2]{\left[\begin{array}{c}#1 \\ #2 \end{array}\right]}$$ $$\newcommand{\threevec}[3]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\cthreevec}[3]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \end{array}\right]}$$ $$\newcommand{\fourvec}[4]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\cfourvec}[4]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \end{array}\right]}$$ $$\newcommand{\fivevec}[5]{\left[\begin{array}{r}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\cfivevec}[5]{\left[\begin{array}{c}#1 \\ #2 \\ #3 \\ #4 \\ #5 \\ \end{array}\right]}$$ $$\newcommand{\mattwo}[4]{\left[\begin{array}{rr}#1 \amp #2 \\ #3 \amp #4 \\ \end{array}\right]}$$ $$\newcommand{\laspan}[1]{\text{Span}\{#1\}}$$ $$\newcommand{\bcal}{\cal B}$$ $$\newcommand{\ccal}{\cal C}$$ $$\newcommand{\scal}{\cal S}$$ $$\newcommand{\wcal}{\cal W}$$ $$\newcommand{\ecal}{\cal E}$$ $$\newcommand{\coords}[2]{\left\{#1\right\}_{#2}}$$ $$\newcommand{\gray}[1]{\color{gray}{#1}}$$ $$\newcommand{\lgray}[1]{\color{lightgray}{#1}}$$ $$\newcommand{\rank}{\operatorname{rank}}$$ $$\newcommand{\row}{\text{Row}}$$ $$\newcommand{\col}{\text{Col}}$$ $$\renewcommand{\row}{\text{Row}}$$ $$\newcommand{\nul}{\text{Nul}}$$ $$\newcommand{\var}{\text{Var}}$$ $$\newcommand{\corr}{\text{corr}}$$ $$\newcommand{\len}[1]{\left|#1\right|}$$ $$\newcommand{\bbar}{\overline{\bvec}}$$ $$\newcommand{\bhat}{\widehat{\bvec}}$$ $$\newcommand{\bperp}{\bvec^\perp}$$ $$\newcommand{\xhat}{\widehat{\xvec}}$$ $$\newcommand{\vhat}{\widehat{\vvec}}$$ $$\newcommand{\uhat}{\widehat{\uvec}}$$ $$\newcommand{\what}{\widehat{\wvec}}$$ $$\newcommand{\Sighat}{\widehat{\Sigma}}$$ $$\newcommand{\lt}{<}$$ $$\newcommand{\gt}{>}$$ $$\newcommand{\amp}{&}$$ $$\definecolor{fillinmathshade}{gray}{0.9}$$

8. $$u(x,t)=\frac{8}{\pi ^{3}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}e^{-(2n-1)^{2}\pi ^{2}t}\sin (2n-1)\pi x$$

9. $$u(x,t)=\frac{4}{\pi}\sum_{n=1}^{\infty}\frac{1}{(2n-1)}e^{-9(2n-1)^{2}\pi ^{2}t/16}\sin\frac{(2n-1)\pi x}{4}$$

10. $$u(x,t)=\frac{\pi}{2}e^{-3t}\sin x-\frac{16}{\pi} \sum_{n=1}^{\infty}\frac{n}{(4n^{2}-1)}e^{-12n^{2}t}\sin 2nx$$

11. $$u(x,t)=-\frac{32}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(1(-1)^{n}2)}{n^{3}}e^{-9n^{2}\pi ^{2}t/4}\sin\frac{n\pi x}{2}$$

12. $$u(x,t)=-\frac{324}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{3}}e^{-4n^{2}\pi ^{2}t/9}\sin\frac{n\pi x}{3}$$

13. $$u(x,t)=\frac{8}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{(2n-1)^{2}}e^{-(2n-1)^{2}\pi ^{2}t}\sin\frac{(2n-1)\pi x}{2}$$

14. $$u(x,t)=-\frac{720}{\pi ^{5}}=-\frac{720}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{5}}e^{-7n^{2}\pi ^{2}t}\sin n\pi x$$

15. $$u(x,t)=\frac{96}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}e^{-5(2n-1)^{2}\pi ^{2}t}\sin (2n-1)\pi x$$

16. $$u(x,t)=-\frac{240}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{5}}e^{-2n^{2}\pi ^{2}t}\sin n\pi x$$

17. $$u(x,t)=\frac{16}{3}+\frac{64}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{2}}e^{-9\pi ^{2}n^{2}t/16}\cos\frac{n\pi x}{4}$$

18. $$u(x,t)=-\frac{8}{3}+\frac{16}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{n^{2}}e^{-n^{2}\pi ^{2}t}\cos\frac{n\pi x}{2}$$

19. $$u(x,t)=\frac{1}{6}-\frac{1}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{n^{2}}e^{-36n^{2}\pi ^{2}t}\cos 2n\pi x$$

20. $$u(x,t)=4-\frac{384}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}e^{-3(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

21. $$u(x,t)=-\frac{28}{5}-\frac{576}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{4}}e^{-5n^{2}\pi ^{2}t/2}\cos\frac{n\pi x}{\sqrt{2}}$$

22. $$u(x,t)=-\frac{2}{5}-\frac{48}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{4}}e^{-3n^{2}\pi ^{2}t}\cos n\pi x$$

23. $$u(x,t)=\frac{3}{5}-\frac{48}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{2+(-1)^{n}}{n^{4}}e^{-n^{2}\pi ^{2}t}\cos n\pi x$$

24. $$u(x,t)=\frac{\pi ^{4}}{30}-3 \sum_{n=1}^{\infty}\frac{1}{n^{4}}e^{-4n^{2}t}\cos 2nx$$

25. $$u(x,t)=\frac{8}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n+1)(2n-3)}e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{ (2n-1)\pi x}{2}$$

26. $$u(x,t)=8 \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[(-1)^{n}+\frac{4}{(2n-1)\pi }\right]e^{-3(2n-1)^{2}t/4}\sin\frac{(2n-1)x}{2}$$

27. $$u(x,t)=\frac{128}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}e^{-5(2n-1)^{2}t/16}\sin\frac{(2n-1)\pi x}{4}$$

28. $$u(x,t)=-\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{4}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{(2n-1)\pi x}{2}$$

29. $$u(x,t)=\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{2}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{(2n-1)\pi x}{2}$$

30. $$u(x,t)=\frac{192}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{4}}e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{(2n-1)\pi x}{2}$$

31. $$u(x,t)=\frac{1536}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{(2n-1)\pi x}{2}$$

32. $$u(x,t)=\frac{384}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{4}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{(2n-1)\pi x}{2}$$

33. $$u(x,t)=-64\sum_{n=1}^{\infty}\frac{e^{-3(2n-1)^{2}t/4}}{(2n-1)^{3}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\cos\frac{(2n-1)x}{2}$$

34. $$u(x,t)=-\frac{16}{\pi}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}e^{-(2n-1)^{2}t}\cos\frac{(2n-1)x}{4}$$

35. $$u(x,t)=-\frac{64}{\pi}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\left[1-\frac{8}{(2n-1)^{2}\pi ^{2}}\right]e^{-9(2n-1)^{2}\pi ^{2}t/64}\cos\frac{(2n-1)\pi x}{8}$$

36. $$u(x,t)=\frac{8}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}e^{-3(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

37. $$u(x,t)=-\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{2}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

38. $$u(x,t)=-\frac{32}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{3}}e^{-7(2n-1)^{2}t/4}\cos\frac{(2n-1)x}{2}$$

39. $$u(x,t)=\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}5+\frac{8}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

40. $$u(x,t)=\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}3+\frac{4}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

41. $$u(x,t)=-\frac{768}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+\frac{(-1)^{n}2}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

42. $$u(x,t)=-\frac{384}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+\frac{(-1)^{n}4}{(2n-1)\pi}\right]e^{-(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

43. $$u(x,t)=\frac{1}{2}-\frac{2}{\pi}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}e^{-(2n-1)^{2}\pi ^{2}a^{2}t/L^{2}}\cos\frac{(2n-1)\pi x}{L}$$

44. $$u(x,t)=\frac{2}{\pi}\sum_{n=1}^{\infty}\frac{1}{n}\left[1-\cos\frac{n\pi}{2}\right]e^{-n^{2}\pi ^{2}a^{2}t/L^{2}}\sin\frac{n\pi x}{L}$$

45. $$u(x,t)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{2n-1}\sin\frac{(2n-1)\pi}{4}e^{-(2n-1)^{2}\pi ^{2}a^{2}t/4L^{2}}\cos\frac{(2n-1)\pi x}{2L}$$

46. $$u(x,t)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{2n-1}\left[1-\cos\frac{(2n-1)\pi}{4}\right]e^{-(2n-1)^{2}\pi ^{2}a^{2}t/4L^{2}}\sin\frac{(2n-1)\pi x}{2L}$$

48. $$u(x,t)=1-x+x^{3}+\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{e^{}-9\pi ^{2}(2n-1)^{2}t/16}{(2n-1)}\sin\frac{(2n-1)\pi x}{4}$$

49. $$u(x,t)=1+x+x^{2}-\frac{8}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{e^{-(2n-1)^{2}\pi ^{2}t}}{(2n-1)^{3}}\sin (2n-1)\pi x$$

50. $$u(x,t)=-1-x+x^{3}+\frac{8}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}e^{-3(2n-1)^{2}\pi ^{2}t/4}\cos\frac{(2n-1)\pi x}{2}$$

51. $$u(x,t)=x^{2}-x-2-\frac{64}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\left[1-\frac{8}{(2n-1)^{2}\pi ^{2}}\right]e^{-9(2n-1)^{2}\pi ^{2}t/64}\cos\frac{(2n-1)\pi x}{8}$$

52. $$u(x,t)=\sin\pi x+\frac{8}{\pi } \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n+1)(2n-3)}e^{-(2n-1)^{2}\pi ^{2}t/4}\sin\frac{(2n-1)\pi x}{2}$$

53. $$u(x,t)=x^{3}-x+3+\frac{32}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{e^{-(2n-1)^{2}\pi ^{2}t/4}}{(2n-1)^{3}}\sin\frac{(2n-1)\pi x}{2}$$

This page titled 11.12: A.12.1- Section 12.1 Answers is shared under a CC BY-NC-SA 3.0 license and was authored, remixed, and/or curated by William F. Trench.